PENGEMBANGAN STRATEGI LEADERSHIP PEMBELAJARAN MEMBACA PERMULAAN UNTUK SISWA KELAS I SD - Machrus Abadi (Pascasarjana Universitas Negeri Malang, 2017)
The main problem in learning to read is how to select and use learning strategies. Learning strategy is a means of interaction in the learning process to be used must lead to good learning activities, thus learning objectives can be maximized. According to Degeng (1989: 141) that teaching delivery strategy refers to methods used to convey the pursuit of the learners as well as to receive and respond to feedback from learners. Strategic leadership is learning to read in the beginning is a learning strategies that use the leadership style developed by the constructivist approach that combines cooperative and contextual learning in teaching. Early reading learning leadership strategy combines small group learning and modeling. Learning begins with a teacher conducting apperception (sing/clap) followed by guessing pictures (animal / object) or letters, syllables, and words through teacher demonstration. Teachers provide stimulus through questions that correspond to the image. Students catch the stimulus by answering questions in a way by mentioning initial letters, syllables or words. Each student who guessed correctly will be given a chance as a reward and a further demonstration models. Each students courage in answering and the courage becomes a model and it is the shape of a leader. Each stimulus of questions made by the students and instruction in group learning is an initiative attitude of a leader to help underprivileged students in learning to read in the beginning. It is expected from learning leadership strategy of early reading can help to make even distribution of student learning through small group and can solve problems in the field of learning to read in the beginning. The objective of this study is to generate products in a form of leadership strategy as a new variation of early reading learning strategy packed in a guideline of strategy implementation. Namely developing the concept of leadership strategy, steps, appropriateness of leadership strategy with the levels of understanding and needs of students class I elementary school. Pokok permasalahan dalam pembelajaran membaca adalah bagaimana memilih dan menggunakan strategi belajar. Strategi belajar merupakan alat interaksi di dalam proses belajar yang digunakan harus menimbulkan aktivitas belajar yang baik sehingga tujuan pembelajaran dapat secara maksimal. Strategi leadership pembelajaran membaca permulaan adalah strategi pembelajaran yang mengunakan gaya kepemimpinan dikembangkan dengan pendekatan konstruktivis yang menggabungkan kooperatif learning dan kontekstual dalam pengajarannya. Strategi leadership pembelajaran membaca permulaan menggabungkan pembelajaran kelompok, kecil, dan modeling. Diharapkan dari strategi leadership pembelajaran membaca permulaan ini dapat membantu pemerataan pembelajaran siswa lewat kelompok kecil dan dapat mengatasi permasalahan pembelajaran membaca permulaan di lapangan. Tujuan penelitian ini adalah menghasilkan produk berupa strategi leadership sebagai variasi baru pembelajaran membaca permulaan yang dikemas dalam sebuah panduan pelaksanaan strategi. Buku panduan tersebut mengembangkan konsep strategi leadership, langkah-langkah, kesesuaian strategi leadership dengan tingkat pemahaman dan kebutuhan siswa kelas I SD.